Process validation for pilot-scale production of Betamethasone 17-valerate emulsions using palm olein as topical drug delivery vehicle - Win, Thazin; Ahmad, Kausar; Bakhtiar, M. Taher; Sarker, Md. Zaidul Islam (Kulliyyah of Pharmacy, International Islamic University Malaysia, 2016)
Almost all base for creams and ointments for drug delivery is mineral oil or derived from mineral oil. This work embarks on the successful use of palm olein emulsion as a vehicle for drug delivery. In contrast, palm olein, which is obtained from palm oil is a renewable source and not exhaustive as mineral oil. Palm olein contains naturally occurring tocopherols and tocotrienols that would assist healing and improve skin condition. The use of palm olein has connotes the support for green technology. Betamethasone 17-valerate is a very potent drug in the treatment of various skin diseases. With palm olein as the base, concentration of betamethasone 17-valerate to achieve similar efficacy is lowered. This is due to enhanced diffusion of the drug from the vehicle. It is thus expected that therapeutic efficiency is improved. Although laboratory scale formulation appears excellent in terms of stability and product quality, scale-up studies using palm olein in pharmaceutical products has never been explored and the problems that may be encountered during pilot-scale production still need to be investigated. This study aims to establish and validate a manufacturing process for scale-up of the products which can ensure the quality as well as stability and batch similarity of the products. The formulations were trademarked as PalmisoneTM and carried out at least three batches of 5 kg lab-scale production and three batches of 80 kg pilot-scale production. The formulations were characterized, subjected to stability studies for a year and degradation of betamethasone 17-valerate in the formulations was analysed using HPLC. The results of lab-scale and pilot-scale formulations were compared to that of three commercially available products. When the qualities of products were satisfactory, the pilot-scale production process was validated through process capability studies according to regulatory guidelines. The manufacturing process was robust and capable of producing products with consistent and desired quality. Pilot-scale PalmisoneTM topical emulsions showed particle size ranging from 3 to 14 μm, viscosity 68.2±1.43 mPa.s, pH 5.8± 0.1 and zeta potential -51 ± 11 mV. Since the product used only halal raw materials with halal certification, PalmisoneTM emulsions are halal products. In conclusion, the knowledge acquired during scale-up process could be of value for further projects which intend to scale-up formulations using palm olein. The use of palm olein added up the advantages of diversifying the use of major commodity of Malaysia to both national and global level as well as also supporting green technology by developing inexhaustible resource.